Konstitutionalistas Perda Syari'ah di Indonesia dalam Kajian Otonomi Daerah - al Arif, M. Yasin; Paramadina, Panggih F. (Universitas Islam Negeri Raden Intan Lampung, 2021)
The rolling of regional autonomy in 1999 was marked by the issuance of Law Number 22 Year 1999 concerning Regional Government and Law No. 25 of 1999 concerning Financial Balance between the Central and Regional Governments, has provided a very strong impetus for the regions to regulate their regions according to the aspirations of the people in the regions. In an instant, the euphoria was manifested by the local elite into legal regulations that tended to be elitist. Now the issue of problematic regional regulations has shifted no longer only with a material tendency, but has spread to the area of choice of the ideology that underlies it, namely the regional regulations with the nuances of Islamic law. The authorship uses a normative juridical research method, in which the author uses laws, journal articles, books and documents that support the analysis related to the constitutionality of sharia regulations. Thus, the sharia regional regulations are substantially inconsistent with the spirit of regional autonomy. Except for areas that are given specificity in carrying out their government. Although the aims and objectives of the formation of these regional regulations are good for improving a reduced moral order, they must be used in a way that is in accordance with the established legal structures. So that by referring to the theory about the level of legal norms and hierarchy that have been determined in Law no. 12 of 2011, the Sharia Regional Regulation substantially contradicts the legal norms that are above it and can be said to be unconstitutional.